Analisis Prinsip Non Diskriminasi Pada Seleksi Penerimaan CPNS Dalam Perspektif HAM - Aca Surya Putra Zai (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
In terms of being a nation and state, Indonesia as a state of law (rechtstaat) is obliged to respect, fulfill and uphold human rights (HAM). Thus, one of the principles that must be implemented by the state (power) is how to create non-discriminatory conditions for every aspect of state life. The principle of non-discrimination is the part that determines the existence of equality, where the principle of non-discrimination seeks that everyone cannot be deprived of their rights only because of external factors (such as skin color, gender, physical form, language, religion, politics, nationality, birth status, and so on). . The benefit of the research discussion is to discuss the hottest issue, where in 2022 there were CPNS selection participants who failed due to various reasons for physical condition factors (having X legs, men with large chests), even though these participants received fairly high test scores compared to other participants, even though in terms of civil and political rights, the state should prioritize the principle of non-discrimination, including in the selection process for the acceptance of Candidates for Civil Servants (CPNS). Whereas Article 11 of Law Number 8 of 2016 concerning Persons with Disabilities states: that persons with disabilities have equal opportunities to obtain jobs organized by the government, regional government and the private sector without discrimination. So it is interesting to study from the side of Human Rights.